“Developing Creativity and Cultural Competence in Children through Folk Applied Arts” - Raxmonova Rayxon Zoir qizi (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: This article explores the significance of folk applied arts in promoting creativity, aesthetic skills, and cultural competence in school-age children. Engaging in practical activities such as creating traditional patterns, crafting ornaments, and experimenting with colors and textures enhances fine motor skills, visual perception, and problem-solving abilities. Integrating folk arts into the curriculum encourages social interaction, collaboration, and appreciation of cultural heritage, offering a holistic approach to child development.